Why imitation matters for a speech and language pathologist? - Saleem, Khadija; Saba Abrar; Muhammad Sikander Ghayas Khan (Journal of the Pakistan Medical Association, 2024)
Dear Editor, I want to shed light on an important preverbal skill “Imitation” for speech Language Pathologists and parents. Imitation arises very early in typical development and serves as a pivotal factor in a baby's acquisition of new skills from infancy, toddler stage, childhood and beyond. Initially, a newborn's abilities, like sucking for feeding, are reflexive and innate, requiring no explicit teaching.1 In typical development, learning to imitate often occurs spontaneously. Observing and mimicking parents, siblings, or peers is how a child learns to navigate various milestones, such as feeding, using the potty, riding a bike, writing, and tying shoes.2. Additionally, imitation plays a significant role in social development, aiding in making friends and learning to interact and play with others. 3 There are many levels of imitation developed by professionals in the form of hierarchy. Organizing them into smaller, achievable steps with practical examples and detailed instructions serves as a helpful reminder.4 The following are the levels of imitation: Level-1: The child will mimic actions with objects Your goal is for the child to mimic listed actions. Demonstrate each action 3 to 5 times, assisting if needed. Use simple language and short phrases. For example; 1-Pop a bubble on the floor with your hand, saying "Pop!" 2-Pop a bubble in the air with your finger, also saying "Pop!" Level-2: The child will mimic movements, gestures, and sign language with bubbles Demonstrate the body movements and gestures for the child to copy. Assist him in performing each gesture after showing him 3 to 5 times. Remember, the child is not expected to talk yet, but your simple and repetitive words are crucial. For example; 1-Kick, stomp, or clap bubbles while saying "Pop!" 2- Then, clap to show excitement after popping bubbles and say "Yayyy (yahoo)." Level-3: The child will mimic facial and mouth movements without speaking while interacting with bubbles Keep it simple and use single words. Emphasize the importance of copying the movements. For example; 1-Blow a bubble and utter "Blow!" 2-Mimic eating a bubble, then say "Eat!" Level-4: Model play sounds for the child to imitate while playing with bubbles together For example 1-Model the sound /p-p-p/ without a vowel as you pop bubbles. 2-Enhance anticipation by audibly inhaling before blowing 5. Dear Editor, by adhering to these guidelines and instructions, parents and professionals alike can initiate therapy effectively, paving the way for success and reaching significant milestones.